A Psychoanalytical Study Of Paul Morel’s Sexual Desire In D.H Lawrence’s Sons And Lovers - Evi Baiturohmah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2020)
This research examines the sexual desire of Paul Morel, a male main character in the D.H Lawrence’s novel Sons and Lovers. It is a descriptive qualitative library research with the main data are the narrative and dialogues taken from the respective novel.The study aims to describe how Paul Morel’s sexual desire in the novel Sons and Lovers is constructed. It uses Freudian psychoanalysis approach to reveal the pattern of intimate relationships between Paul Morel and three most- significant women in his life: Gertrude Morel, Miriam Leviers, and Clara Dawes. The result of the study shows that Paul sexual desire is constructed by his relationship with three women characters that posit different effects to him. Paul experiences Oedipus complex when he is a child. The mother acts as the restraining force that restricts Paul from fulfilling his sexual desire with other women. Paul and Miriam’s relationship is the manifestation of the id versus the superego. There’s an endless battle between Paul’s raw desire and Miriam’s religiosity. Meanwhile Paul and Clara’s relationship is the realization of the id. The intimacy between them is solely based on pleasure principle and satisfaction pursuit.  Keywords: id, ego, psychoanalysis, sexual desire, superego